(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
Crustacea is a diverse group of arthropods that includes familiar organisms such as crabs, lobsters, shrimp, crayfish, and barnacles, as well as many other less well-known species. They are found in marine, freshwater, and terrestrial environments and are characterized by a hard exoskeleton, jointed limbs, and two pairs of antennae.Crustaceans range in size from tiny planktonic copepods to the giant Japanese spider crab, which can have a leg span of up to 4 meters. Many species are important both ecologically and economically, serving as food sources for larger organisms or as valuable seafood for humans.Crustaceans have a variety of feeding strategies, including filter feeding, scavenging, and predation. They are also known for their complex behaviors and communication methods, such as chemical signaling and visual displays.The reproductive strategies of crustaceans vary widely depending on the species, with some laying thousands of eggs at once and others carrying their eggs on their bodies until they hatch. Many crustaceans also undergo complex developmental stages, such as metamorphosis, during their life cycle